Eksekusi Barang Jaminan Fidusia Penyebab Timbulnya Masalah Hukum - Hidayat, Syaiful; Geraldo, Jendri; Nasir, Muh (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
A Consumer Financing Agreement is a legal construct derived from a lease agreement. Acquiring motor vehicles through instalment purchases is advantageous for low-income, fragile economies. A Consumer Agreement with a fiduciary guarantee allows an individual to acquire a motor vehicle without immediate cash payment to enhance their operating activity. Nonetheless, executing this Consumer Financing Agreement encounters numerous challenges, as customers/debtors cannot meet their instalment obligations as per the designated schedule, resulting in adverse credit outcomes and the enforcement of goods subject to fiduciary guarantees. This study informs the public that collateral enforcement must be conducted through the judicial system and cannot be arbitrary. This study employs Analytical Descriptive Research, which involves elucidating a specific issue at a designated time and location where